Meninjau Perilaku Bullying Terhadap Kepercayaan Diri Remaja SMP Se-Kota Bekasi - Wahyu Aulizalsini Alurmei; Annisa Erniyanti; Arsyadani hasanah; Milani Nabila Syahra; Thalia Amelinda Setiawan (Politeknik Kampar, 2024)
Bullying is a behavior that is carried out verbally, physically or psychologically against a person or group of people. This bullying often happens anywhere and at any time. The aim is to overcome the impact that arises from bullying behavior, as well as how much influence bullying behavior has on self-confidence, which will also determine the role of counselors in handling bullying cases. To determine the counseling approach given to victims of bullying. This research used 20 SMP X students aged 12-15 years as subjects. The sampling technique is random sampling. The data collection method used was a questionnaire with a Self-Confidence Scale and a Bullying Scale. The overall results show that there is no significant difference between bullying behavior and self-confidence of SMP X students, but most of the filling is done by female students. This can be considered a special concern because female students will be more sensitive regarding feelings. The results of the data analysis show the moderate category which of course still requires prevention to prevent bullying behavior which can later reduce the level of self-confidence in students.